Diagnosis of the leukemic phase of ALK-positive anaplastic large cell lymphoma by immunohistochemistry on cell block prepared from peripheral blood buffy coat - Aditi Kundoo; Madhusmita Sethy; Mukund N Sable; Pritinanda Mishra; Asuthosh Panigrahi; Amit K Adhya (Wolters Kluwer Medknow Publications, 2020)
A leukemic phase of anaplastic lymphoma kinase positive anaplastic large cell lymphoma (ALK+ ALCL) is rare. The leukemic cells morphologically appear as small to intermediate-sized cells with cerebriform and cloverleaf-like nuclei and are misdiagnosed as other T-Cell lymphomas/leukemia with similar morphology. We describe a case where the diagnosis of leukemic ALK+ ALCL was aided by immunohistochemistry performed on the cell blocks prepared from the peripheral blood buffy coat specimen. The diagnosis of ALK+ ALCL was further confirmed on the biopsy of a cutaneous nodule of this patient. We found the method of immunohistochemistry on peripheral blood buffy coat cell block very useful and suggest that it may be used as an alternative method to flowcytometry in low resource settings.